EXPLORING THE THEORY OF ARCHETYPES - Ahunjanova , Mohinur Sohibjon qizi; Botirova , Zebo (Educational Research in Universal Sciences, 2023)
This article explores the key concepts of the Theiry of Archetypes and its significance in understanding the human experience. The Theory of Archetypes, known as “Arxetiplar nazariyasi” in Uzbek, delves into the fundamental patterns and symbols that are ingrained in the collective human psyche.